Etheostoma erythrozonum, a new species of darter (Teleostei: Percidae) from the Meramec River drainage, Missouri - Switzer, John F.; Wood, Robert M. (Zootaxa, 2009)
A new species of darter, Etheostoma erythrozonum, is described from the Meramec River drainage of Missouri, USA. Etheostoma erythrozonum is the first known fish species endemic to the Meramec River drainage. It differs morphologically and genetically from populations of its sister species, Etheostoma tetrazonum, from the Gasconade River, Osage River, and Moreau River drainages.